Thinkers of the twentieth century (Chicago, 1987)
The book presents thinkers of the 20th century from the fields of science, mathematics and literature. The entry of each thinker comprises a biography, a bibliography, a listing of critical studies on the entrant, and a signed, critical essay
Keywords: biography- 20th century,scholars - biography